Milk-sharing experiences: Perspective among Malaysian donors and rexipient mothers - Jamil, Nurul Akma; Khuan, Lee; Ai Theng, Cheong; Muda, Siti Mariam (Jurnal Keperawatan Padjadjaran, 2025)
Background: Shared breastmilk has been a longstanding tradition in many cultures throughout history through wet nursing, cross nursing, and the donation of expressed breastmilk to a milk bank. However, social media has introduced some new dynamics to this practice, making it more visible and accessible; and it is known as milk-sharing. Research on milk sharing is still in its infancy and focused on western perspectives. Therefore, the sociocultural dimensions of milk sharing have not been adequately explored across different settings and cultures.   Purpose: This qualitative study aims at understanding the milk-sharing experiences among donor and recipient mothers in Malaysia.   Methods: We conducted a social media analysis on milk-sharing postings from four Facebook Groups Pages. This was followed by a detailed exploration of individual experiences throughout the milk-sharing journey using a semi-structured, online interview with thirty mothers. Thematic analysis was applied in the data analysis process using ATLAS.ti 9 software.   Results: A total of 252 postings were retrieved from four Facebook Groups Pages. Of these, 151 postings referred to donating milk, 70 referred to requesting milk, and 31 focused on issues related to milk-sharing. Thirty mothers with various milk-sharing experiences were involved in this study. Fifteen donors, six recipients, and nine fell into both categories. The mothers in the study had an average age of 32.9 years and the majority were Malay. In terms of their relationship with the infants, 93.3% were biological mothers with the majority having two to five children. Thematic analysis identified five themes: 1) point of reference, 2) communication platform, 3) altruism for mutual benefit, 4) faith and 5) challenges and problem-solving methods.   Conclusions: Milk sharing is a personal and sociocultural-bounded practice where mothers negotiate their understanding of the need to breastfeed and the use of donated breastmilk. Despite its specific focus on the Malaysian context, this research offers a complementary understanding of milk sharing within a non-Western framework and transferable to similar sociocultural backgrounds. The findings are important for intercultural nursing and midwifery practice, where nurses can incorporate sociocultural perspectives into breastmilk donation initiatives to increase public acceptance.